Impact of air pollution on agricultural productivity in urban area - Fitriana, Nasya Aulia; Lutpi, Nabilah Aminah; Abdeljawad, Nour Salah (Environmental and Toxicology Management, 2024)
Introduction: Air pollution in urban environments impacts biodiversity, and disrupts ecosystem services that are essential for urban dwellers. One of the significant impacts of air pollution is on agricultural productivity in urban areas. Methods: This study used a quantitative approach with a descriptive design. The aim was to analyze plant responses to air pollution. Results: Air pollutants such as tropospheric ozone can damage plant tissues and disrupt cell functions, including photosynthesis and respiration, resulting in decreased growth and yield. Air pollution can disrupt pollination and fruit and seed formation, reducing the quantity and quality of the crop. Pollutants such as carbon monoxide (CO), nitrogen dioxide (NO2), and sulfur dioxide (SO2) affect plant physiology and morphology, including stomata damage, decreased chlorophyll, and leaf growth. Conclusion: The results of the study indicate that air pollution can damage plant tissues and disrupt cell functions, including photosynthesis and respiration, resulting in decreased growth and yield.